1991
DOI: 10.1093/ageing/20.2.124
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular Skin Responses in Elderly People with Varicose Leg Ulcers

Abstract: The function of cutaneous primary afferent unmyelinated nerves (C-fibres) was assessed by measuring axon reflex vasodilatation in the skin over the arms and feet of 15 elderly patients with chronic venous ulcers using a laser Doppler flowmeter. Dilatation of skin microvasculature in response to nerve-independent stimuli was also assessed. Results were compared with those of control subjects matched for age and sex. The chronic venous ulcer group showed reduced axon reflex vasodilatation in the feet but not the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 0 publications
1
11
1
Order By: Relevance
“…Local neuro-vascular mechanisms, including the sympathetic nervous system, cause vasoconstriction in response to venous hypertension and thus buffer the rise in capillary pressure and transudation of fluid into the surrounding tissues. There have been various reports that the venoarteriolar reflex is either intact [15] or impaired [16] in patients with ISVI, the latter possibly due in part to a form of neuropathy affecting small unmyelinated C-fibres in patients with venous disease [17]. In the present study, however, ISVI had no effect on the normal vasoconstrictor response to standing.…”
Section: Discussioncontrasting
confidence: 69%
“…Local neuro-vascular mechanisms, including the sympathetic nervous system, cause vasoconstriction in response to venous hypertension and thus buffer the rise in capillary pressure and transudation of fluid into the surrounding tissues. There have been various reports that the venoarteriolar reflex is either intact [15] or impaired [16] in patients with ISVI, the latter possibly due in part to a form of neuropathy affecting small unmyelinated C-fibres in patients with venous disease [17]. In the present study, however, ISVI had no effect on the normal vasoconstrictor response to standing.…”
Section: Discussioncontrasting
confidence: 69%
“…Aging affects vascular system and causes changes in structure and function (1) such as impairment of endothelium‐dependent vasodilation (2), reduced α‐adrenoceptor responsiveness (3), reduced β‐adrenergic sensitivity (4), and a reduction in the neurogenic inflammatory responses (5). In the human dental pulp, histologic studies have shown age‐related changes (6, 7), e.g.…”
mentioning
confidence: 99%
“…This is a sympathetic reflex and loss implies a sympathetic neuropathy. Ardron et al [12] suggested there was a ''C'' Evidence of neuropathy comes from recently conducted clinical studies by Padberg et al [13] and Reinhardt et al [14]. Padberg et al [13] suggested that the involvement of the deep tendon reflexes implied a global effect of CVI rather than a purely local phenomenon.…”
Section: Discussionmentioning
confidence: 99%